2008
DOI: 10.1094/mpmi-21-2-0178
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and Functional Effects Caused by Various Viral RNA Silencing Suppressors in Transgenic Nicotiana benthamiana and N. tabacum

Abstract: RNA silencing suppressor genes derived from six virus genera were transformed into Nicotiana benthamiana and N. tabacum plants. These suppressors were P1 of Rice yellow mottle virus (RYMV), P1 of Cocksfoot mottle virus, P19 of Tomato bushy stunt virus, P25 of Potato virus X, HcPro of Potato virus Y (strain N), 2b of Cucumber mosaic virus (strain Kin), and AC2 of African cassava mosaic virus (ACMV). HcPro caused the most severe phenotypes in both Nicotiana spp. AC2 also produced severe effects in N. tabacum but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 53 publications
7
54
0
5
Order By: Relevance
“…In these transgenic plants, GFP silencing can be triggered by transient GFP expression by Agrobacterium infiltration ( Johansen & Carrington, 2001), whereas RNA-silencing suppressors, which initiate post-transcriptional gene silencing, can rescue transient expression of GFP in the infiltrated regions. Our results show that transient expression of TAV2b suppressed GFP silencing and rescued the expression of GFP (Fig 3, lower left spot on each leaf), similar to suppression by the P19 proteins (Fig 3, upper right spot on each leaf; Siddiqui et al, 2008). As a negative control, GFP protein expression was almost completely suppressed when the GFP transgene was infiltrated alone (Fig 3, upper left spot on each leaf).…”
Section: Tav2b Suppresses Rna Silencingsupporting
confidence: 60%
“…In these transgenic plants, GFP silencing can be triggered by transient GFP expression by Agrobacterium infiltration ( Johansen & Carrington, 2001), whereas RNA-silencing suppressors, which initiate post-transcriptional gene silencing, can rescue transient expression of GFP in the infiltrated regions. Our results show that transient expression of TAV2b suppressed GFP silencing and rescued the expression of GFP (Fig 3, lower left spot on each leaf), similar to suppression by the P19 proteins (Fig 3, upper right spot on each leaf; Siddiqui et al, 2008). As a negative control, GFP protein expression was almost completely suppressed when the GFP transgene was infiltrated alone (Fig 3, upper left spot on each leaf).…”
Section: Tav2b Suppresses Rna Silencingsupporting
confidence: 60%
“…It has been suggested that symptoms in potyvirus-infected plants are associated at least to some extent with the RNA-silencing suppressor activity of the HC-Pro protein that interferes with endogenous microRNA (miRNA) accumulation, causes misregulation of the expression of several miRNA-regulated transcription factors, and produces developmental defects in transgenic plants (66). Similarly, transgenic expression of the silencing suppressor protein of PVX, P25, produced developmental alterations in N. benthamiana (67). Thus, PVX-PVY-associated synergism could partly be caused by the combined effect of both suppressors on several RNA-regulated networks.…”
Section: Discussionmentioning
confidence: 99%
“…The P25 transgene also prevented recovery of N. benthamiana from systemic TRSV infection, but it did not allow the systemic infection of TRSV in the transgenic N. tabacum host at elevated temperatures. This failure in this Nicotiana species was probably due to the low expression level of the transgene in this line (Siddiqui et al, 2008). On the other hand, it is conceivable that the P25 protein function itself is temperature-sensitive, as indicated by the results of Close (1964) and Xie et al (2001).…”
Section: Effects Of Silencing Suppressors On Trsv Infectionmentioning
confidence: 91%